Expenditure Levels, Prices and Consumption Patterns in a Cross-Sectioin of Countries - Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2001)
This paper uses data on consumption expenditure and price levels from the European Comparison Project (ECP) 1996 for the analysis of demand structures in a cross-section of 52 countries. The paper describes the patterns of consumption expenditures, price levels and relative prices for four groups of countries (ranked by their expenditure levels). This is done at different levels of aggregation for three, six, and eight groups of consumption goods. This descriptive analysis shows, first, the dependence of consumption patterns on the level of expenditures and, second, broad patterns of price levels and price structures. Poorer countries tend to have lower absolute price levels in all groups of goods examined. It turns out that e.g. the relative price of food tends to be higher the lower the per capita income of a country is. On the other hand, services tend to be relatively cheaper in low income countries. Two models of demand are tested econometrically. The Workings model uses only expenditure levels as the independent variable to explain the patterns of consumption. It is shown especially for some goods that this sole explanatory variable gives a surprisingly good fit in explaining the consumption structures across countries. Further the Almost Ideal Demand System (AIDS), which is a quite flexible framework for estimating consumption structures and includes also prices as explaining variables, is tested econometrically for various aggregates of consumption goods (three and six commodity groups) in a cross-country analysis. The results given in this paper derived from the non-linear as well as a linearized version of the model confirms the results from other studies using time-series data (especially the results found by Deaton and Muellbauer, 1980a). The results in general show that a large proportion of the variation in consumption patterns across countries can be explained by expenditure (income) levels and prices.
Keywords: C31; C52; D12; O57; 330; consumption patterns; demand analysis; price levels; price structures; demand systems